The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1111/tid.13829
|View full text |Cite
|
Sign up to set email alerts
|

Into the unknown: Diagnosing mysterious brain lesions

Abstract: In this inaugural clinicopathological conference, the invited experts discussed the diagnostic approach to central nervous system infections in immunocompromised hosts.The case presented involved a pancreas-kidney transplant recipient with multiple brain abscesses caused by Bartonella henselae. CSF metagenomic next-generation sequencing played a significant role in the diagnosis. Bartonella henselae is a gramnegative zoonotic pathogen that causes cat-scratch disease, which can be transmitted to humans through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…However, granulomatous inflammation of the brain tissue involving meningitis has been demonstrated by some investigators ( 14 , 15 ), and the histopathological features of direct infection by Bartonella henselae were the same as those in the case of our study. Furthermore, there have been some previous reports of brain abscesses and leptomeningitis related to the infection of Bartonella henselae ( 16 18 ). Hence, a bacterial invasion may be a continuous process of CSD involving the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…However, granulomatous inflammation of the brain tissue involving meningitis has been demonstrated by some investigators ( 14 , 15 ), and the histopathological features of direct infection by Bartonella henselae were the same as those in the case of our study. Furthermore, there have been some previous reports of brain abscesses and leptomeningitis related to the infection of Bartonella henselae ( 16 18 ). Hence, a bacterial invasion may be a continuous process of CSD involving the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, and for diagnostic purposes, blood has been the primary target sample type for the detection of Bartonella species in reservoir hosts and incidentally infected patients. Although few reports describe the detection of Bartonella DNA from other body fluids such as serum [ 56 , 81 ], cerebrospinal fluid (CSF) [ 82 , 83 ], lymph node aspirates [ 84 ], aqueous humor [ 85 ], urine [ 86 ], and saliva [ 64 , 65 , 86 , 87 ], to our knowledge, a systematic assessment of the viability of this or other Bartonella species in these diagnostic patient fluid specimens has not been undertaken. Historically, case reports describing people acquiring CSD from rose thorn injuries [ 88 ], as well as cat or dog salivary transmission from bites and scratches [ 89 , 90 , 91 ], point to this organism’s ability to tolerate a wide range of environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Only reports published in English were included. A total of ve studies were found that mention the application of mNGS in the diagnosis of CSD using different types of samples (Table 1), including lymph node tissue, tissue swabs, plasma, peripheral blood and cerebrospinal uid (8)(9)(10)(11)(12) . Although the clinical manifestations, B. henselae-speci c sequences identi ed using mNGS and genome coverage varied considerably among the studies, they all proved that mNGS is an e cient method for establishing a pathogenic diagnosis in cases of complicated general infection.…”
Section: Discussionmentioning
confidence: 99%